Το χρονικό της ανακάλυψης μιας ελληνιστικής πόλης στην Καρία (Bucakkoy, Συνέτα) - Χανιώτης, Άγγελος (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1997)
In the winter of 1995, an inscribed stele found near the village of Bucakköy in Karia was transported to the Aphrodisias Museum. The stele is dedicated to Zeus Synetenos by a priest and 121 other men (late 3rd or early 2nd cent. B.C.). The epithet Synetenos belongs to a widespread type of Anatolian divine epithets, which usually derive from place names. The village of Bucakköy has been known as the possible site of a smal independent polis ever since the discovery of an honorific inscription, built into the wall of the village mosque, in 1893. K. Buresch (1895), J.G.C. Anderson (1897), and Jeanne and Louis Robert (1946) recorded the presence of an ancient cemetery, a late Roman site, two inscriptions, and a relief representation of a mother goddess, but were unable to find evidence for the exact location or the name of the city. In light of the new epigraphic find C. Ratté, L. Bier, and A. Chaniotis undertook an investigation, which offered answers to both questions. A fragmentary inscription (3rd/2nd cent.) was found built in the wall of a house in Bucakköy. It contains the last 9 lines of an honorific decree; in the hortatory formula, where one expects the name of the community, we find a word beginning with the letters SY, obviously the ethnic name Synetenoi. This confirms the assumption that the city’s name was Syneta (cf. other indigenous names, such as Anineta, Azita, etc.). The city itself was discovered at the hilltop site of Tola§ Tepe, where the dedicatory inscription was found. This polis, in the eastern end of the Maeander valley and at the border of Phrygia and Karia, may have been founded by the Seleucids (late 3rd cent.) or the Attalids (early 2nd cent.). The rich onomastic material indicates that its population consisted of settlers from the coastal cities of Ionia. It is an attractive assumption - in the light of the small size of the settlement, the fact that the dedicatory inscription does not give any information about the identity of the 122 dedicators, and the fact that only a few men seem to have family relations with one another - that these men were the first settlers.